The Role of Pre-service Training for Civil Servants Group III: Perspective of Regulation of the Head of the State Administration Agency Number 15 2015 Regarding Banjarmasin Religious Education and Training Center - Muhammad Yudil Khairi (Universitas Muhammadiyah Sidoarjo, 2020)
Education and training are activities that are designed to prepare new employees, to be better prepared to carry out work, or to be organized to develop old employees so that they are more able to develop their potential. To form a new professional Civil Servants (PNS), there needs to be an update on the current pattern of education and training. The practice of conducting Pre-service Training with classical learning patterns is more dominated by lecture methods, making it difficult to form the basic values of the PNS profession, especially the internalization process in each of the Pre-service Training participants. The focus or subject of this research is all parties involved in the implementation of Regular Group III Pre-service Training in South Kalimantan, Central Kalimantan and East Kalimantan, which took place on 28 September to 30 October 2015 at Banjarmasin Religious Education and Training Center. This research uses a descriptive qualitative approach. The results of this study indicate that the Banjarmasin Religious Training Center has implemented the Head of State Administrative Agency Regulation No. 15 of 2015 concerning Guidelines for Organizing Education and Training of Pre-Service Candidates for Civil Servants Group III quite effectively. This can be seen from the 10 SOPs regarding the implementation of Education and Training; there are only 3 SOPs that have not been appropriately implemented. Factors influencing the implementation of Regulation of the Head of State Administration Number 15 of 2015 concerning Guidelines for Providing Education and Training for Civil Servant Candidates for Class III in the form of lack of socialization, relations between organizations are not optimal and limited resources can still be improved for the implementation of Training and Education that will become.